Embedding Virtual and Augmented Reality in Higher Education in Yemeni Universities - Nagi, Gawed; Al-Fuhaidi, Belal (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Virtual reality (VR) and augmented reality (AR) have increasingly applied to different areas including medicine, engineering, advertising, tourism, entertainment, training, and education. Although VR and AR are still new and not yet used in higher education in Yemen, many colleges and universities worldwide have implemented multimedia and VR/AR technologies as promising learning tools. VR/AR technologies effectively add more engagement, motivation, retention, satisfaction, and enjoyment into learning process when compared to the traditional teaching and learning methods. The aim of the paper is to highlight the uses of VR and AR in different scenarios in many areas and more specifically in higher education and distance learning. In this paper, simple models are proposed and presented to help universities and policymakers in Yemen adopt these innovative technologies and encourage them to invest more resources and training towards implementing those technologies within their curriculum.